The effect of adding colostrum or sodium butyrate to the diet on the intestinal barrier of weaned piglets - Marek Pieszka; Kinga Szczepanik; Paweł Kubica; Maria Oczkowicz; Sylwia Orczewska-Dudek; Bogadan Śliwiński; Łukasz Gala (PLoS ONE, 2026)
Weaning is a critical stage for piglets, often leading to intestinal barrier disruption, impaired nutrient absorption, and growth reduction. This study investigated the effects of dietary supplementation with dried bovine colostrum or sodium butyrate on intestinal barrier function, nutrient absorption, and growth performance in weaned piglets. Eighteen DanBred Hybrid piglets (28 days old) were allocated to three groups (n = 6): control (no additive), colostrum, and sodium butyrate. Piglets were fed standardized prestarter and starter diets for 28 days. Growth performance and feed conversion ratio (FCR) were monitored, and intestinal permeability was assessed using a sugar absorption test with LC-MS/MS analysis of urinary sugars. Additional evaluations included intestinal histomorphometry, brush border enzyme activities, immunohistochemistry for tight junction proteins, hematological and biochemical parameters, and gene expression analysis. Colostrum supplementation resulted in significantly higher final body weight and average daily gain compared with control and sodium butyrate groups (P < 0.001). FCR was consistently improved in the colostrum group during both feeding phases. Sugar absorption tests indicated greater urinary recovery of mannitol, lactulose, sucrose, and raffinose, suggesting enhanced intestinal permeability and nutrient uptake. Histological analysis showed longer jejunal villi and increased mucosal width (P < 0.01). Colostrum-fed piglets also exhibited higher sucrase and lactase activities and upregulated expression of occludin and claudin 5. Sodium butyrate produced positive but less pronounced effects, including increased claudin 1 expression in the ileum and dipeptidylpeptidase IV activity. Hematological parameters remained within reference ranges, with lower gamma-glutamyl transferase levels observed in the colostrum group, indicating reduced metabolic stress. No major differences were found in cytokine gene expression. In summary, spray-dried bovine colostrum supports gut health and metabolism in weaned piglets by enhancing intestinal barrier maturation. It boosts digestive enzyme activity and nutrient utilization, which contributes to improved growth. Sodium butyrate provided supportive but less consistent benefits. Overall, bovine colostrum represents a practical and effective nutritional strategy to improve the health and development of piglets after weaning.